THE CONSEPT OF CREATION OF EDUCATIONAL AND RESEARCH TRAINING PROGRAM ON THE EDUCATIONAL AND SCIENTIFIC LEVEL – DOCTOR OF PHILOSOPHY (PhD) - Kolomiyets, S.; Synekop, O. (Continuing Professional Education: Theory and Practice, 2019)
The problem of the concept creation of education and research training program on the educational and scientific level – Doctor of Philosophy (PhD) is considered; the factors of the creation of educational and research training program are identified; the purpose and set of goals are outlined; learning principles (sustainable development and education, international integration and integration of Ukraine higher education in the European Higher Education Area, the continuity of the process of higher education and openness, scientific approach, interdisciplinary connections, integration of theory and practice, systematicity and consistency, consciousness and activity, variability, critical self-assessment, scientific creativity) in the preparation of humanities scholars are detailed; the content of educational and research training program is substantiated; competencies (research, professional-methodical, research-strategic) are defined; the abilities, knowledge and skills are highlighted; invariant and variable components of the educational process are considered.